On interval observer design for active Fault Tolerant Control of Linear Parameter-Varying systems - Lamouchi, Rihab; Raissi, Tarek; Amairi, Messaoud; Aoun, Mohamed (Systems & control letters, 2022)
This paper proposes an active Fault Tolerant Control (FTC) scheme for polytopic uncertain Linear Parameter-Varying (LPV) systems subject to uncertainties and actuator faults. First, a fault estimation interval observer is designed to estimate the system state and the actuator fault. A novel approach is developed using the L∞ norm to attenuate the effects of the uncertainties and to improve the accuracy of the proposed observer. Then, based on the fault estimation information, the FTC strategy is designed using a linear state feedback control law and H∞ technique to compensate actuator faults and maintain system performance and stability, even under faulty conditions. Finally, the effectiveness of the proposed method is demonstrated by its application to a vehicle lateral dynamic nonlinear model. •Fault Tolerant Control using interval state estimation and robust stabilization.•Set-membership framework for the design of Linear Parameter Varying systems.•Fault estimation observer design for descriptor system.•L∞ norm-based design method to attenuate the effect of fault and uncertainties and to improve the estimation performance.